2022
DOI: 10.4314/tjpr.v21i9.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined use of home blood pressure monitoring and nifedipine on blood pressure compliance and quality of life of patients with essential hypertension

Abstract: Purpose: To investigate the effect of combination of home blood pressure monitoring (HBPM) and nifedipine on blood pressure compliance and quality of life in patients with essential hypertension. Methods: One hundred and twenty essential hypertension patients admitted to Jiaozuo Coal Industry (Group) Co. Ltd Central Hospital from February 2020 to February 2021 were retrospectively studied. They were equally divided into study group (SG) and control group (COG) according to the order of admission. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…A total of 46 RCTs involving 8 ginkgo-based proprietary CPMs and 5183 participants were included in this study, including 21 items of ginkgo biloba tablet (GBT), [22–42] 3 items of GB capsule (GBC), [43–45] 6 items of ginkgo biloba drop (GBD), [46–51] 3 items of ginkgo biloba ketone ester drop (GBKED), [18,52,53] 2 items of Fufangyinxing capsule (FFYX), [54,55] 2 items of fufangyinxingtongmai oral liquid (FFYXTM), [56,57] 2 items of Yinxingmihuan oral liquid (YXMH), [58,59] and 7 items of Yindanxinanotong softgel capsule (YDXNT). [60–66] The basic characteristics of the included literature such as authors, time of publication, subject information (mean age, gender), interventions, duration of treatment, duration of follow-up, and outcome indicators are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 46 RCTs involving 8 ginkgo-based proprietary CPMs and 5183 participants were included in this study, including 21 items of ginkgo biloba tablet (GBT), [22–42] 3 items of GB capsule (GBC), [43–45] 6 items of ginkgo biloba drop (GBD), [46–51] 3 items of ginkgo biloba ketone ester drop (GBKED), [18,52,53] 2 items of Fufangyinxing capsule (FFYX), [54,55] 2 items of fufangyinxingtongmai oral liquid (FFYXTM), [56,57] 2 items of Yinxingmihuan oral liquid (YXMH), [58,59] and 7 items of Yindanxinanotong softgel capsule (YDXNT). [60–66] The basic characteristics of the included literature such as authors, time of publication, subject information (mean age, gender), interventions, duration of treatment, duration of follow-up, and outcome indicators are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-six studies reported comparable baseline information between groups. Forty-four studies [18,22–41,43–57,59–66] did not mention blinding, 1 study [58] utilized double blinding, and 1 study [42] was single blinded. Regarding the outcome section, 45 studies [22–28,30–50] used tables combined with text to record the outcome indicators of the researchers, and 1 study [29] used textual descriptions, and none of them had missing outcome data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations